1999
DOI: 10.1889/1.1834134
|View full text |Cite
|
Sign up to set email alerts
|

Fringe‐Field Effects In Reflective CMOS LCD Design Optimization

Abstract: Reflective CMOS LCD light valves have high brightness and high information content. Unlike direct view displays, microdisplays also have interpixel spacing several time smaller than the cell gap. This in combination with the small pixel formats lead to fringe‐field effects having a significant impact on the effective display brightness and contrast of μLCD's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Our study also showed a regular VA operation can be obtained in the direct-view LCD, but not in the microdisplay geometry. The results showed a small crossed talk and small edge disclination images from the LC reverse titled orientation for the direct-view VA LCD, but a large crossed-talk, large LC reverse titled combined with large twist orientation for the microdisplay VA geometry [15,[20][21][22][23][24]. This is consistent with experimental observation results.…”
Section: Discussionsupporting
confidence: 88%
“…Our study also showed a regular VA operation can be obtained in the direct-view LCD, but not in the microdisplay geometry. The results showed a small crossed talk and small edge disclination images from the LC reverse titled orientation for the direct-view VA LCD, but a large crossed-talk, large LC reverse titled combined with large twist orientation for the microdisplay VA geometry [15,[20][21][22][23][24]. This is consistent with experimental observation results.…”
Section: Discussionsupporting
confidence: 88%
“…The ability to resolve the edge of the pixel is related to the LC gap. The thicker the gap, the greater the influence of fringe-field effects [5]. So to maintain resolution the LC gap should be significantly less than the pixel size.…”
Section: The Lcos Panelmentioning
confidence: 99%
“…6 The VA mode exhibits an unprecedented contrast ratio, but it suffers from a serious fringing field effect from adjacent pixels. [7][8][9] As a result, each bright pixel is split into two unequal parts separated by a dark line. This split pixel decreases the optical efficiency to ϳ70%.…”
Section: Introductionmentioning
confidence: 99%